Psychological Well-Being Sebagai Prediktor Tingkat Kesepian Mahasiswa - Janice Grace Lusiani Larasati Simanjuntak; Clement Eko Prasetio; Firza Yusani Tanjung; Airin Triwahyuni (Jurnal Psikologi Teori dan Terapan, 2021)
Loneliness leads to several health risks, especially among university students who are prone to experience it. In order to cope with loneliness, university students need functional psychological resources, which can be measured by six-dimensional of psychological well-being (PWB) by Ryff. Thus, this study aims to predict university students loneliness using the multidimensional PWB. Loneliness was measured using Revised UCLA Loneliness Scale and PWB was measured using Ryffs multi-dimensional PWB. A total number of 376 undergradute students in Faculty of Psychology Universitas Padjadjaran Indonesia were participated in this study. The test of correlation using Pearsons r resulted all dimensions were negatively correlated. Stepwise regression analysis resulted that positive relationship, self-acceptance, environmental mastery, and autonomy were the significant predictors, predicted 74.7% of the variance, of loneliness among participants. These findings indicate that dimensions mentioned can be used as predictors of university students loneliness.Keywords: Loneliness, psychological well-being, university students Abstrak: Kesepian dapat memicu berbagai risiko kesehatan, terutama bagi mahasiswa yang rentan mengalaminya. Untuk menghadapi kesepian, mahasiswa memerlukan keberfungsian psikologis yang dapat ditandai oleh tingkat psychological well-being (PWB) oleh Ryff. Maka dari itu, penelitian ini bertujuan untuk memprediksi tingkat kesepian dengan menggunakan PWB multidimensional. Tingkat kesepian diukur dengan kuesioner Revised UCLA Loneliness Scale, sementara tingkat PWB diukur dengan kuesioner PWB multidimensional dari Ryff. Sebanyak 376 mahasiswa tingkat sarjana Fakultas Psikologi Universitas Padjadjaran Indonesia berpartisipasi. Uji korelasi (r) Pearson menunjukkan semua dimensi PWB berkorelasi negatif dengan kesepian. Analisis regresi stepwise menunjukkan prediktor terkuat adalah dimensi relasi positif, penerimaan diri, penguasaan lingkungan, dan otonomi, memprediksi 74,7% varians tingkat kesepian. Hasil ini mengindikasikan bahwa keempat dimensi tersebut dapat digunakan sebagai prediktor tingkat kesepian pada mahasiswa.